2005
DOI: 10.1007/s10620-005-2651-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori Infection in Male Patients with Osteoporosis and Controls

Abstract: Cytokines that regulate bone turnover (tumor necrosis factor-alpha, interleukin-6, etc.) may influence the pathogenesis of skeleton disorders, such as osteoporosis. Since Helicobacter pylori infection increases the systemic levels of inflammatory cytokines, we investigated the possibility that this infection increases the risk of developing osteoporosis and affects the bone metabolism in a group of male patients with osteoporosis. We examined 80 osteoporotic male patients and 160 controls for serum antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 24 publications
3
50
0
1
Order By: Relevance
“…Figura et al 18) evaluated 80 osteoporotic males, and 160 healthy males for antibodies to HP, hormone levels and bone turnover markers and measured HP strains expressing Cag A antibodies in HP seropositive patients and controls. They found that HP seropositivity was not different but Cag A expressing HP seropositivity was significantly different between groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figura et al 18) evaluated 80 osteoporotic males, and 160 healthy males for antibodies to HP, hormone levels and bone turnover markers and measured HP strains expressing Cag A antibodies in HP seropositive patients and controls. They found that HP seropositivity was not different but Cag A expressing HP seropositivity was significantly different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…They found that HP seropositivity was not different but Cag A expressing HP seropositivity was significantly different between groups. Therefore, Figura et al 18) proposed that HP strains expressing Cag A might increase the risk of osteoporosis in male patients by reducing the systemic levels of estrogens. They also proposed that bone resorption in patients infected with Cag A-positive HP strains, was higher than in those infected with Cag A-negative HP strains and HP negative cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone alteration may be related to the underlying gastric disease. The prevalence of H pylori infection has been found to be high in men with osteoporosis, 62 and this infection may be present in patients taking ASDs. H pylori infection can induce a permanent infl ammatory response, that is, a gastric and systemic increase in indexes of infl ammation.…”
Section: Acid -Suppr Es Sive Drugs a Nd Fr Ac T Ur E Riskmentioning
confidence: 99%
“…This mechanism has been implicated in some extragastric manifestations in H pylori-infected patients. 62 A major limitation of our meta-analysis of observational studies is the possibility of uncontrolled confounding. Our fi ndings should therefore be confi rmed by further prospective studies including RCTs that are designed specifi cally with large sample sizes and long follow-up durations to test the effect of ASDs on the risk of fracture.…”
Section: Acid -Suppr Es Sive Drugs a Nd Fr Ac T Ur E Riskmentioning
confidence: 99%